A Prospective Clinical Trial Comparing Surgical Fixation Versus Nonoperative Management of Minimally Displaced Complete Lateral Compression Pelvis Fractures. Issue 11 (November 2021) - Slobogean, Gerard P.; Gaski, Greg E.; Nascone, Jason; Sciadini, Marcus F.; Natoli, Roman M.; Manson, Theodore T.; Lebrun, Christopher; McKinley, Todd; Virkus, Walter W.; Sorkin, Anthony T.; Brown, Krista; Howe, Andrea; et al.
Abstract : Objective: To compare the early pain and functional outcomes of operative fixation versus nonoperative management for minimally displaced complete lateral compression (LC; OTA/AO 61-B1/B2) pelvic fractures. Design: Prospective clinical trial. Setting: Two academic trauma centers. Patients: Forty-eight adult patients with LC pelvic ring injuries with <10 mm of displacement were treated nonoperatively and 47 with surgical fixation. Sixty percent of participants were randomized. Seventy-three percent of the fractures were displaced <5 mm, and 71% were LC-1 patterns. Intervention: Operative fixation versus nonoperative management. Main Outcome Measurements: The primary outcome was patient-reported pain using the 10-point Brief Pain Inventory. Functional outcome was measured using the Majeed pelvic score. Outcomes were analyzed using hierarchical Bayesian models to compare the average treatment effect from injury to 12 and 52 weeks postinjury. The probability of the mean treatment benefit exceeding a clinically important difference was determined. Results: The 3-month average treatment effect of surgery compared with nonoperative management was a 1.2-point reduction in pain [95% credible interval (CrI): 0.4–1.9] and an 8% absolute improvement in the Majeed score (95% CrI: 3%–14%). Similar results persisted to 1 year. Patients with initial fracture displacement ≥5 mm experienced a larger reduction in pain (2.2, 95% CrI: 0.9–3.5) compared with those patients with less initial displacement (0.9, 95% CrI: 0.1–1.8). Conclusion: On average, surgical fixation likely provides a small improvement in pain and functional outcome for up to 12 months. Patients with ≥5 mm of posterior pelvic ring displacement are more likely to experience clinically important improvements in pain. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.